2021
DOI: 10.1186/s41239-021-00273-y
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effect of three scaffoldings on the collaborative problem-solving processes in China’s higher education

Abstract: Collaborative problem-solving (CPS) engages students in solving ill-structured problems, creating group knowledge, and developing self-regulation and collaboration skills. Different scaffoldings, such as minimal-guided, task-oriented, and idea-oriented, can be used to facilitate students’ CPS activities, but their effects have not been comprehensively explored. In this research, we use minimally-guided, task-oriented, and idea-oriented scaffoldings to promote Chinese university students’ online CPS activities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 66 publications
(89 reference statements)
0
12
0
Order By: Relevance
“…Metacognitive scaffolding originates from the concept of metacognition, the thinking about and reflection on one's cognitive processing (Ouyang et al, 2021;Winne & Azevedo, 2014). To support collaborative learning, metacognition is extended from the individual level to the social context, e.g., group metacognition (GM) (Biasutti & Frate, 2018) and socially shared regulation of learning (SSRL) (Hadwin et al, 2018).…”
Section: Group-level Metacognitive Scaffoldingmentioning
confidence: 99%
See 1 more Smart Citation
“…Metacognitive scaffolding originates from the concept of metacognition, the thinking about and reflection on one's cognitive processing (Ouyang et al, 2021;Winne & Azevedo, 2014). To support collaborative learning, metacognition is extended from the individual level to the social context, e.g., group metacognition (GM) (Biasutti & Frate, 2018) and socially shared regulation of learning (SSRL) (Hadwin et al, 2018).…”
Section: Group-level Metacognitive Scaffoldingmentioning
confidence: 99%
“…Previous CSCL studies have promoted the use of mixed methods to understand collaborative effectiveness and collaborative learning processes and outcomes (Janssen et al., 2013; Medina & Stahl, 2020; Stahl, 2009). For example, the statistical analysis, sequential analysis, and social network analysis approaches have been used to investigate correlations between collaborative variables (Zemel et al., 2009), sequences of students’ knowledge contributions (Chen et al., 2017) and social interaction structures and participatory roles (Ouyang & Chang, 2019; Ouyang & Scharber, 2017). Moreover, qualitative, ethnographic approaches (e.g., discourse analysis, observation, or interview) have also been used to examine the micro-level relevancies of collaborative activities and students’ actions during collaboration or perceptions about collaboration (Stahl, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Instructors should take advantage of instructional design, facilitation strategies, and technological supports to foster students’ practice of group cognition. First, during instructional design of collaborative learning activities, instructors can consider to provide students with choices to negotiate the collaborative purposes and procedures; when students view themselves as creators of the collaboration, they may be more prone to develop collective responsibility, joint actions and shared epistemic agency (Damşa, 2014; Ouyang, Chen, Cheng, et al., 2021; Ouyang & Chang, 2019). Students are more likely to form equal, interdependent participations with a shared, collective agency in the group, which is beneficial for students to develop group cognition.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to a traditional class where the instructor takes a substantive leader role to design and guide the instruction and learning, the instructor needs to transfer their roles to maintain a balance between instructor authority and student meaning making and facilitate the high quality of collaboration (Nel, 2017; Ouyang & Scharber, 2017; Robinson et al, 2019). Previous research has indicated that varied scaffoldings have been provided by the instructors to facilitate CSCL, such as cognitive scaffoldings (Tabak & Baumgartner, 2004; van de Pol et al, 2019), metacognitive scaffoldings (Ben-David & Zohar, 2009; Ouyang et al, 2021), and socio-emotional scaffoldings (Ouyang et al, 2020; Park et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Ben-David and Zohar (2009) found that metacognitive hints stimulated the student groups’ discussions through sharing ideas to group members and asking follow-up questions. Ouyang et al (2021) compared the effects of three metacognitive scaffoldings (i.e., minimal-guided scaffolding, the task-oriented scaffolding, and the idea-oriented scaffolding) on students’ collaborative performances, processes, and perceptions. Results found that when the instructor provided metacognitive scaffoldings related to the ideas and perspectives, students’ cognitive contribution, metacognitive regulation, and knowledge artifact behaviors strengthened.…”
Section: Literature Reviewmentioning
confidence: 99%